Dietary supplementation with spray-dried animal plasma improves vaccine protection in aged mice - Miró, Lluïsa; Rosell-Cardona, Cristina; Amat, Concepció; Polo, Javier; Moretó, Miquel; Pérez-Bosque, Anna (Frontiers in Nutrition, 2023)
Senescence is characterized by an aggravated inflammatory state that reduces vaccine responsiveness. Dietary supplementation with spray-dried porcine plasma (SDP) exerts anti-inflammatory effects in different mucosal areas. We aimed to determine if the anti-inflammatory properties of SDP improve the efficiency of immunization in senescent animals. Experiments were performed in 2-month-old and 6-month-old male SAMP8 mice fed control or SDP (8%) feeds for 4 months. The mice received nasal doses of 2.5 μg of S. aureus enterotoxin B (SEB) or vehicle every 15 days (i.e., 3 times). Fifteen days after the last dose, a lethal shock was induced by intraperitoneal administration of SEB and LPS. Immunization increased anti-SEB IgA in intestinal and bronchoalveolar fluid (P<0.05). After the lethal shock, all immunized aged mice that were supplemented with SDP survived, in contrast to only 66% of those fed the control feed (P<0.05). Moreover, after the lethal challenge, aged mice showed higher expression levels of pro-inflammatory cytokines (Il-6, Tnf-α, Ifn-γ, and Il-1β) in jejunal and (Tnf-α, and Il-1β) in lung tissues (P<0.05), which were reduced by SDP supplementation (P<0.05). Furthermore, SDP supplementation augmented Il-4 and Il-10 expression in both tissue types (P<0.05). In conclusion, SDP reduces the mucosal inflammation associated with aging, improving vaccine protection in senescent mice.